Athenian and Alexandrian Neoplatonism and the harmonization of Aristotle and Plato - Hadot, Ilsetraut. (Studies in Platonism, Neoplatonism, and the Platonic Tradition, 2015)
Athenian and Alexandrian Neoplatonism and the Harmonization of Aristotle and Plato by I. Hadot deals with the Neoplatonist tendency to harmonize the philosophies of Plato and Aristotle. It shows that this harmonizing tendency, born in Middle Platonism, prevailed in Neoplatonism from Porphyry and Iamblichus, where it persisted until the end of this philosophy. Hadot aims to illustrate that it is not the different schools themselves, for instance those of Athens and Alexandria, that differ from one another by the intensity of the will to harmonization, but groups of philosophers within these schools.